2019
DOI: 10.1161/circresaha.119.314876
|View full text |Cite
|
Sign up to set email alerts
|

The Human-Specific and Smooth Muscle Cell-Enriched LncRNA SMILR Promotes Proliferation by Regulating Mitotic CENPF mRNA and Drives Cell-Cycle Progression Which Can Be Targeted to Limit Vascular Remodeling

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 54 publications
(69 reference statements)
2
116
0
Order By: Relevance
“…Arterial inflammation occurs very early in atherogenesis and is associated with impairment of many salutary functions of the healthy endothelium. Accumulating studies point to lncRNAs as regulators of endothelial homeostasis, smooth muscle cell contractility, and macrophage-mediated inflammation in the vessel wall (11,13,(15)(16)(17)(18). This study provides evidence for the first time to our knowledge that the mouse-specific lncRNA VINAS and its human ortholog, DEPDC4, play important roles in vascular inflammation and atherogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…Arterial inflammation occurs very early in atherogenesis and is associated with impairment of many salutary functions of the healthy endothelium. Accumulating studies point to lncRNAs as regulators of endothelial homeostasis, smooth muscle cell contractility, and macrophage-mediated inflammation in the vessel wall (11,13,(15)(16)(17)(18). This study provides evidence for the first time to our knowledge that the mouse-specific lncRNA VINAS and its human ortholog, DEPDC4, play important roles in vascular inflammation and atherogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…Lee K et al identified 914 DEGs between stable and ruptured plaques by using microarray technology, and highlighted the involvement of FABP4 and leptin in the progression of atherosclerosis and plaque rupture (Lee et al, 2013). Mahmoud AD et al revealed the DEGs between stable and unstable plaques, which were mainly linked with the plaque instability, including inflammation, matrix remodeling, and calcification (Mahmoud et al, 2019). Although these studies revealed some molecular mechanisms of the atherosclerosis development in various aspects, they could not reveal the cell-specific mechanisms, such as foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSE41571 (Lee et al, 2013) contains data on 11 macrophage-rich regions from five ruptured plaques and six stable plaques. GSE120521 (Mahmoud et al, 2019) consists of an RNA-seq profile of four stable and four unstable plaque samples. The analysis strategy is shown in Fig.…”
Section: Data Resourcesmentioning
confidence: 99%
“…Further, lncRNA MIAT were detected to be elevated in the blood of ischemic stroke patients [85]. LncRNA SMILR seems to play a role in plaque stability [58], and its plasma levels positively correlate with C-reactive protein [59]. SNPs in the lncRNA MIAT promoter correlated with acute myocardial infarction in a Chinese Han population [86], while a specific polymorphism in MALAT1 (rs619586AG/GG) might be CVD protective [87].…”
Section: Lncrnas As Biomarkers In Atherosclerosismentioning
confidence: 97%
“…One example for lncRNA-mRNA interaction is lncRNA SMILR (smooth muscle–induced lncRNA). SMILR did directly bind the mRNA of the mitotic protein CENPF (centromere protein F) and promoted the proliferation of VSMCs [ 58 ]. In agreement with VSMC proliferation conferring with plaque stability, increased SMILR levels were detected in unstable compared with stable human atherosclerotic plaques [ 59 ].…”
Section: Lncrna-rna Interactions In Atherosclerosismentioning
confidence: 99%